FRAMING TRUMP: A METAPHORIC ANALYSIS OF IRANIAN MAINSTREAM NEWS - Azeri Matin, Alireza (International Journal of Humanity Studies (IJHS), 2023)
Donald J. Trump’s victory in the 2016 presidential election marked the beginning of a gloomy era for Iran-US relations which consequently brought about a series of economic and political consequences, most notably the international sanctions imposed on Iran. As the key player in these political affairs, Trump made several radical decisions involving Iran, provoking the Islamic regime’s harsh and insolent rejoinders which were directed at the US president’s personality. Being largely of a metaphoric nature, such negative remarks recurrently appeared across the state-run national media, constructing a particular social reality about the 45th President of the United States. This was in particular less challenging for the state, considering the general public in Iran had minimum knowledge about Trump before his election in 2016. Using Lakoff and Johnson’s theoretical framework, and investigating the use of metaphors in political news articles published in some of the government’s prominent online news agencies, this study reveals how such rhetorical devices are employed for framing Trump. Ultimately, the findings point to the idea that national media in Iran have craftily taken advantage of culturally embedded concepts to sway public perceptions against Trump, as part of the regime’s anti-west political agenda.